Symbiotic Algae of Hydra viridissima Play a Key Role in Maintaining Homeostatic Bacterial Colonization - Bathia, Jay; Schröder, Katja; Fraune, Sebastian; Lachnit, Tim; Rosenstiel, Philip; Bosch, Thomas C. G. (Frontiers in Microbiology, 2022)
The freshwater polyp Hydra viridissima harbors endosymbiotic Chlorella algae in addition to a species-specific microbiome. The molecular basis of the symbiosis between Hydra and Chlorella has been characterized to be metabolic in nature. Here we studied the interaction between the extracellularly located microbiota and the algal photobiont, which resides in Hydra´s endodermal epithelium, with main focus on Legionella bacterium. We aimed at evaluating the influence of the symbiotic algae on microbial colonization and in shaping the host microbiome. We report that the microbiome composition of symbiotic and aposymbiotic (algae free) H. viridissima is significantly different and dominated by Legionella sp. Hvir in aposymbiotic animals. Co-cultivation of these animals resulted in horizontal transmission of Legionella sp. Hvir bacteria from aposymbiotic to symbiotic animals. Acquisition of this bacterium increased the release of algae into ambient water. From there algae could subsequently be taken up again by the aposymbiotic animals. The presence of algal symbionts had negative impact on Legionella sp. Hvir and resulted in a decrease of the relative abundance of this bacterium. Prolonged co-cultivation ultimately resulted in the disappearance of the Legionella sp. Hvir bacterium from the Hydra tissue. Our observations suggest an important role of the photobiont in controlling an invasive species in a metacommunity and thereby shaping the microbiome.